A importância de conteúdos desenvolvidos no ensino básico para o aprendizado das equações diferenciais - Sant Anna, Debora Cervellini [UNIFESP] (2020)
In this project we will study the differential equations of firts and seond orders, highlighting the contents of basic education that are extremely important for the learning of differential equations. We will approach problem situations differential equations. I hope that at the end of this work you can help and clarify the elementary school teachers how important are the contents taught by them in the education of the exact sciences professional.